2020
DOI: 10.1186/s41937-020-00056-8
|View full text |Cite
|
Sign up to set email alerts
|

A lockdown index to assess the economic impact of the coronavirus

Abstract: Like most countries, the Swiss government adopted drastic measures to stop the spread of the coronavirus. These measures were aimed at avoiding close physical proximity between people. The adverse economic consequences of this lockdown policy became immediately apparent, with almost two million workers, or more than every third worker in Switzerland, being put on short-time work within only 6 weeks after the policy's implementation. In an attempt to promptly assess the heterogeneous consequences of this lockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 11 publications
(8 reference statements)
0
38
0
1
Order By: Relevance
“…Several studies have recently examined the responses to the COVID-19 pandemic in different countries. They adopted different perspectives, analyzing the effectiveness of governmental policies ( Dergiades et al, 2020 ; Desson et al, 2020 ), epidemiological responses ( Jefferies et al, 2020 ), testing, contact tracing and isolation ( Salathe et al, 2020 ), lockdown policy ( Faber et al, 2020 ), preparation of the healthcare sector ( Barro et al, 2020 ), as well as key learned lessons ( Han et al, 2020 ). However, empirical studies of how such measures are perceived by the healthcare staff, and of how the pandemic has affected their work situation from their own perspective, are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently examined the responses to the COVID-19 pandemic in different countries. They adopted different perspectives, analyzing the effectiveness of governmental policies ( Dergiades et al, 2020 ; Desson et al, 2020 ), epidemiological responses ( Jefferies et al, 2020 ), testing, contact tracing and isolation ( Salathe et al, 2020 ), lockdown policy ( Faber et al, 2020 ), preparation of the healthcare sector ( Barro et al, 2020 ), as well as key learned lessons ( Han et al, 2020 ). However, empirical studies of how such measures are perceived by the healthcare staff, and of how the pandemic has affected their work situation from their own perspective, are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…1.4 Literature on work-related consequences, policy, and adherence to guidelines The impact of the COVID-19 pandemic on healthcare systems, as well as the reactions by healthcare institutions and governments, have been the subject of several recent studies from different countries. These studies have focused on topics such as the initial preparation and first reaction after the outbreak, [20] strategies of contact tracing and isolation as the pandemic evolved, [21] protective equipment for healthcare staff, [22] work risks in the healthcare sector, [23] lockdown measures, [24] governmental policy effectiveness, [25,26] and key lessons to be learned. [27] Nevertheless, our study closes a gap by focusing specifically on healthcare workers/students and their experiences, assessment, and knowledge as a source of quantitative empirical information, while such data is still scarce: Spiller et al [12] found that hours worked by Swiss healthcare workers had increased during the height of the first pandemic wave but afterward did not fully converge back to the levels before the pandemic.…”
Section: Literature On Knowledge Risk Perception and Emotional Distmentioning
confidence: 99%
“…To ensure exogeneity, our preferred measures are a lockdown index, which relies on physical proximity, and a home office index, which relies on the possibility to perform tasks at home. Faber, Ghisletta, and Schmidheiny ( 2020 ) built the index by using the Occupational Information Network ( ONET ) survey, which asks workers questions about the level of physical proximity that is required in their occupation. Individual survey answers are translated into an index that is available for economic sectors within cantons, yielding a total of 469 groups.…”
Section: Datamentioning
confidence: 99%
“…The lowest index values are found in sectors, such as financial and insurance activities, or agriculture, whereas the highest values are found in sectors such as accommodation or construction. 24 Faber et al (2020 ) also compute a home office index with the ONET survey. The home office index can be used as an alternative measure of lockdown restrictions.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation